Corporate policies to protect against disinformation for young audiences: the case of TikTok - Quintas-Froufe, Natalia; González-Neira, Ana; Fiaño-Salinas, Carlota (Frontiers in Communication, 2024)
Disinformation and fake news have become highly prevalent on social networks. As such, many platforms have tried to reduce audience exposure to false or erroneous data by implementing corporate policies to protect users. This is especially relevant in social networks aimed at young people, as is the case of TikTok. In recent years, such mediums have become more popular than news sites among young audiences. The purpose of this article is to analyze what these policies are, on what topics they are implemented and how they are being monitored and enforced by the social network TikTok during the period 2020-24. Nonetheless, it must also be mentioned that it is still too early to make a complete and comprehensive assessment of the effectiveness of these policies because many of them are not yet fully implemented.